Resistensi Majelis Luhur Kepercayaan Terhadap Tuhan Yang Maha Esa Indonesia (MLKI) dalam Mempertahankan Keyakinan yang Dianut - Zulkifli, Muhammad; Budiaman, Budiaman; Scorviana, Nova (Edukasi IPS, 2019)
This research aims to: To know the process of resistance that occurs in the community of Penghayat Kepercayaan. To find solution for solving social problems especially inter-religious discrimination in Indonesia. This research conducted at Secretariat of MLKI, Lubang Buaya, East Jakarta. The methodology of this research is qualitative approach, data collected technique by interview, observation, and literature review. Data analysis ofthis research use data reduction, data display, conclusion and verification. Based on the result of this research it is known that discrimination occur against Penghayat Kepercayaan. Therefore Penghayat Kepercayaan do resistance against government policy and attempted to remove negative stigma that attached to them. Resistance which is conducted tend to closed resistance and opened resistance. Keyword: Resistence, Penghayat Kepercayaan, Majelis Luhur Kepercayaan Terhadap Tuhan Yang Maha Esa Indonesia (MLKI), Beliefs